Glycoproteins of herpes simplex virus type 2 as defined by monoclonal antibodies. - Balachandran, N (1982)
We used monoclonal antibodies reacting with glycoproteins specified by herpes simplex virus type 2 (HSV-2) to characterize the individual antigens in terms of structure, processing, and kinetics of synthesis in BHK or Vero infected cells. Our results provided a direct demonstration of the structural identity of the gA and gB proteins of HSV-2 as well as confirmation of the existence of type-specific and type-common domains within the gD molecule. They also show that, with the exception of gC, processing of the viral glycoproteins differs to some extent in Vero and BHK infected cells, possibly as a result of different efficiency of glycosylation or different processing of underglycosylated and unglycosylated products in the two cell types. Finally, we showed that individual HSV-2 glycoproteins are synthesized at greatly different times during the infectious cycle, possibly in response to their different roles in virus replication and assembly.